Quote:
Originally Posted by fun2come
I think we need to redo 423
sum (3 cubed) + sum ((2+1) squared) = 423
20 squared + sum (3! +1) = 428
|
Now I see. Another duplicate one slipped through my quality control.
sum(30) - sum(2 cubed) = 429
sum(30) - sum(2 cubed) + 1 = 430
20 squared + 31 = 431
20 squared + (3 - 1) to the fifth = 432
sum (3 cubed) + sum(10) = 433
sum (3 cubed) + sum(sum(2 squared)) + 1 = 434
sum(30 - 1) = 435
3 * (10 squared) + sum(2 to the fourth) = 436
summation (30 - 1) + 2 = 437
21 squared - 3 = 438
summation (30 - 1) + 2 squared = 439
((sum(3!)) squared) - 1 = 440
21 squared = 441
((sum(3!)) squared) + 1 = 442
((sum(3!)) squared) + 2 = 443
21 squared + 3 = 444